The effect of e-portfolio assessment on EFL vocabulary learning and retention - Nava Nourdad; Mohammad Amin Banagozar (Indonesian Journal of Applied Linguistics, 2022)
Vocabulary is one of the main components in learning a new language which provides the ground for language learners to learn and use the language. In this regard e-portfolio, as a recent and novel assessment technique, can have the potential for vocabulary development. This study aimed at investigating the effect of portfolio assessment on Iranian EFL guidance school learners’ vocabulary learning and retention. To this end, 92 guidance school students in the seventh, eighth, and ninth grades, were selected as the participants of the study. They were randomly assigned into two experimental and control groups. While the control group followed the conventional class quizzes the experimental group practiced e-portfolio assessment. The participants in the experimental group were asked to create their e-portfolios and keep a record of what they learned during and after the online sessions. They were also asked to include the reflection sheets in their e-portfolios. Three parallel tests as a pre-test, an immediate post-test, and a delayed post-post were used to gather data about the effect of portfolio assessment in each grade (a total of nine tests). The results of a one-way ANCOVA revealed that the participants of the experimental group outperformed the participants of the control group in terms of EFL vocabulary learning and retention. Considering the outcomes, the study presents some implications for practitioners including language teachers, curriculum and course developers, and language learners.